The Internalization of Pawongan Values in Roald Dahl’s The Giraffe, the Pelly and Me - Putu Virna Yanti; Ni Komang Arie Suwastini; Ni Wayan Surya Mahayanti (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2026)
This study examines how the Pawongan values of Tri Hita Karana are reflected in Roald Dahl’s The Giraffe, the Pelly, and Me. While previous studies have explored moral values in children’s literature, few have interpreted Western literary works through the lens of Balinese local wisdom and their relevance to English as a Foreign Language (EFL) learning. Addressing this gap, this study employs an interpretive qualitative approach using the interactive data analysis model of Miles, Huberman, and Saldaña. Data were collected through close reading and classified into sequences and sub-sequences to identify social interactions among the characters. The findings reveal that respect, helpfulness, cooperation, caring, appreciation, and perseverance consistently reflect the Pawongan values in fostering social harmony. The novelty of this study lies in applying the Tri Hita Karana framework to interpret a Western children’s novel. These findings suggest that the novel can serve as culturally responsive EFL teaching material that integrates Balinese local wisdom with character education.   Studi ini mengkaji bagaimana nilai-nilai Pawongan dari Tri Hita Karana tercermin dalam The Giraffe, the Pelly, and Me, karya Roald Dahl. Sementara penelitian sebelumnya telah mengeksplorasi nilai-nilai moral dalam sastra anak-anak, hanya sedikit yang menafsirkan karya sastra Barat melalui lensa kearifan lokal Bali dan relevansinya dengan pembelajaran bahasa Inggris sebagai Bahasa Asing (EFL). Mengatasi kesenjangan ini, penelitian ini menggunakan pendekatan kualitatif interpretatif menggunakan model analisis data interaktif Miles, Huberman, dan Saldaña. Data dikumpulkan melalui pembacaan dekat dan diklasifikasikan ke dalam urutan dan sub-urutan untuk mengidentifikasi interaksi sosial di antara karakter. Temuan tersebut mengungkapkan bahwa rasa hormat, suka membantu, kerja sama, kepedulian, penghargaan, dan ketekunan secara konsisten mencerminkan nilai-nilai Pawongan dalam menumbuhkan kerukunan sosial. Kebaruan penelitian ini terletak pada penerapan kerangka Tri Hita Karana untuk menafsirkan novel anak-anak Barat. Temuan ini menunjukkan bahwa novel ini dapat berfungsi sebagai bahan ajar EFL yang responsif secara budaya yang mengintegrasikan kearifan lokal Bali dengan pendidikan karakter.